Fraud Diamond Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Indeks IDX80 Periode 2019-2023 - Suryananda, Leonardi; Khairani, Siti (Universitas Multi Data Palembang, 2025)
The purpose of this study was to determine how the fraud diamond model affects financial statement fraud. Jones modified model discretionary accruals as a proxy for financial statement fraud. The fraud diamond model consists of financial pressure, opportunity, rationalization, and ability. IDX80 companies listed on the IDX for the 2019-2023 period as the research population. The sampling used by the research was purposive sampling method so that 265 samples were obtained from 53 IDX80 companies. The E-Views 12 Student Version program is used to estimate panel data regression. The results showed that financial pressure, opportunity, and rationalization had an effect on financial statement fraud. Meanwhile, ability has no effect on financial statement fraud.